Exploring the Photophysical Properties of Uio-67 Mof Doped with Rhenium Carbonyl Complexes - Godoy-Gonzalez, F; Godoy-Gonzalez, F; Flores-Vergara, E; Flores-Vergara, E (Elsevier B.V., 2022)
Directly coordinating transition metal catalysts to the linkers of stable metal organic frameworks (MOFs) is a sleek solution to increasing the longevity of the catalyst. Photoluminescence metal complexes incorporated in MOFs have risen in interest lately. Particularly, Re(bpydc)(CO)3Cl (bpydc = 2,2’-bipyridine-5,5’-dicarboxylic acid) doped zirconium-based MOFs (Re-UiO-67) and their use in the photocatalytic reduction of CO2 have attracted considerable attention. Nonetheless, the photophysical characteristics of Re-UiO-67 as a function of loading have not been well explored. Here we analyzed the structural and compositional properties of Re-UiO-67 and showed that the photoluminescence properties of rhenium doped MOFs, including emission intensity, maximum, and lifetime, can be tuned by changing the rhenium loading. The photoluminescence of the film made of Re-UiO-67 exposed to different vapors also exhibited vapoluminescence, luminescence vapochromism, and vapotemporism. Understanding of photophysical properties of the Re-doped MOFs material could provide guidance for further photocatalytic, solar energy conversion and sensing applications. © 2022